MetaDamage tool: Examining post-mortem damage in sedaDNA on a metagenomic scale - Everett, Rosie; Cribdon, Becky (Frontiers in Ecology and Evolution, 2023)
The use of metagenomic datasets to support ancient sedimentary DNA (sedaDNA) for palaeoecological reconstruction has been demonstrated to be a powerful tool to understand multi-organism responses to climatic shifts and events. Authentication remains integral to the ancient DNA discipline and this extends to sedaDNA analysis. Furthermore, distinguishing authentic sedaDNA from contamination or modern material also allows for a better understanding of broader questions in sedaDNA research, such as formation processes, source and catchment and post-depositional processes. Existing tools for detection of damage signal are designed for single-taxon input, require a priori organism specification, and need a significant number of input sequences to establish a signal. It is therefore often difficult to identify an established cytosine deamination rate consistent with ancient DNA across a sediment sample. In this paper we present MetaDamage: a tool that examines cytosine deamination on a metagenomic (all organisms) scale for multiple previously undetermined taxa and can produce a damage profile based on a few hundred reads. We outline the development and testing of the MetaDamage tool using both authentic sedaDNA sequences and simulated data to demonstrate the resolution in which MetaDamage can identify deamination levels consistent with the presence of ancient DNA. The MetaDamage tool offers a method for initial assessment of the presence of sedaDNA and for better understanding key questions of preservation for palaeoecological reconstruction.